Pengaruh Solvabilitas (Debt to Equity Ratio), Profitabilitas (Return on Asset), Ukuran Perusahaan Terhadap Audit Delay - Kiki Muhammad Romli; Sjarif, Devyanthi (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to examine whether there is an influence of return on asset, debt to equity ratio, and company size on Audit Delay. The research population is Properties and Real Estate and Infrastructures companies listed on the Indonesia Stock Exchange from 2016 to 2023. The number of samples in this study were 26 company that fit the criteria. The sampling technique uses purposive sampling method. The research method used is quantitative with secondary data sources. The methode of data analysis uses multiple linear regression analysis with SPSS version 27. Partial research results show that return on assets and company size have an effect on Audit Delay, while debt to equity ratio has no effect on Audit Delay. The results of the study simultaneously show that all variables affect Audit Delay.